Early detection of community acquired of SARS-CoV-2 lineage B.1.351 in Hong Kong - Tsang, Alan K.L. (Journal of Clinical Virology Plus, 2021)
BACKGROUND: Prior to this report, variants of concern for SARS-CoV-2 were only detected from imported cases in Hong Kong. OBJECTIVE: Multiple cases of SARS-CoV-2 lineage B.1.351 have been identified in local community. We reported the phylogenetic relationship of these cases. STUDY DESIGN: SARS-CoV-2 cases were screened for the key non-synonymous substitutions in spike protein by different assays. Preliminary positive cases were further tested by whole genome sequencing. RESULTS: From Dec 2020 to May 2021, 55 SARS-CoV-2 cases belonged to lineage B.1.351. Among them, eight genomes were clustered together, all of them were local cases with epidemiological link. CONCLUSIONS: To track variants of SARS-CoV-2 and to allow early implementation of control measures, SARS-CoV-2 genomic surveillance must be consistently performed.